ANALISIS WACANA PRESIDENTIAL LECTURE OLEH B.J HABIBIE (Kajian Analisis Wacana Kritis) - , Wakhid Nugroho, Prof. Dr. Soepomo Poedjosoedarmo. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research discusses about critical discourse analysis on presidential lecture delivered by B.J Habibie. In this research, the data used is presidential lecture text delivered by B.J Habibie in celebrating of the 62nd Universitas Gadjah Mada Dies Natalis and the 30th of post graduate. This research is interesting because, first, the speech delivered by Habibie is such kind of respond toward reformist community, and that speech is in the form of apology discourse. The method of data collection was done by using observing method, followed by recording and taking note technique. In this analysis, the researcher uses Djikâs approach is to know discourse structure and uses Roger Fowler approach which focuses on content analysis. This approach is to answer about the form and the function of sentence arrangement, and to explain the interest, the researcher uses both. The finding of this study shows that, Habibie uses macro structure as the way to support the main theme, supra structure is to control message structure, and micro structure is to show his achievement background. In the level of transitive using form has function to show the clear relation among agent, goal, and behaver, and intransitive is in the contrary, it does not involve behaver, because the focus is on the attendance of agent and the goal. in the using of the passive voice serves to accentuate the presence of the subject and express disappointed and anger. In positive and negative sentence have the function to perform negation. Rational value is in the form of sentence mode and positive interrogative sentence have the function is to lead public opinion, and the imperative sentence has the function is to have someone else do something. In modalities aspects, intentional modality is to show the \"desire\", \"hope\", \"invitation\", \"omission\", and \"demand\", the epistemic modality is used to express the knowledge, conviction, beliefs, or speakerâs opinions about proposition expressed, deontic modality has the meaning to require, permit, and prohibit the occurrence of an event or action, and dynamic modality serves to express willingness or ability to do something. The interest of macro structure is to support big theme, supra structure is to get audience sympathy, in micro structure as detail is to control the information, as presupposition is to show the optimism, passive sentence is show his powerless to defend strategically industry, cause and effect coherence is to strengthen of strategical industry establishment, Distinct coherence is to classify, distinction coherence is to show distinction level and to strengthen his basic argument, then the interest of transitive is to show clear relation among agent, goal, and behaver. the interest of intransitive is to show unclear relation of cause and effect and to emphasize the subject attendance. The interest of positive and negative sentence is to have the negation well it is to deny or disavow opposition statement. The interest of interrogative and declarative sentence is to give apology, and imperative is to have the audience know about his achievement history, and is to convince the audience. The interest of intentional modality is to express disappointment, is to show his commitment, epistemic modality is to express belief, deontic modality is to give suggestion or prohibition , and the last is dynamic modality is to show the ability or the power of Indonesia to compete with other country.